2014
DOI: 10.3389/fendo.2014.00056
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Reactive Oxygen Species in the Spermatogenesis Regulation

Abstract: Spermatogenesis is a complex process of male germ cells proliferation and maturation from diploid spermatogonia, through meiosis, to mature haploid spermatozoa. The process involves dynamic interactions between the developing germ cells and their supporting Sertoli cells. The gonadal tissue, with abundance of highly unsaturated fatty acids, high rates of cell division, and variety of testis enzymes results very vulnerable to the overexpression of reactive oxygen species (ROS). In order to address this risk, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
142
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 29 publications
0
142
1
1
Order By: Relevance
“…Whereas the role of ROS in the reproductive male function has been widely studied [33][34][35][36][37], only in last few years attention of researchers has been also focused on the female reproductive function. It is believed that ROS over-production in the reproductive tract may significantly contribute to woman infertility mainly because of the ability of these molecules to exert a toxic effect decreasing oocyte quality [2,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the role of ROS in the reproductive male function has been widely studied [33][34][35][36][37], only in last few years attention of researchers has been also focused on the female reproductive function. It is believed that ROS over-production in the reproductive tract may significantly contribute to woman infertility mainly because of the ability of these molecules to exert a toxic effect decreasing oocyte quality [2,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to endocrine dysfunction, several studies suggest that oxidative stress appears to be a key determinant of toxicity induced by ZEA in vivo and in vitro [11,12], and the enzymes of the glutathione system seem to have an important role in spermatogenesis [13]. Reduced glutathione (GSH) itself is a critical factor in maintaining the cellular redox balance and has been demonstrated to be involved in the regulation of cell signaling and repair pathways [13].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced glutathione (GSH) itself is a critical factor in maintaining the cellular redox balance and has been demonstrated to be involved in the regulation of cell signaling and repair pathways [13]. The cellular levels of GSH are controlled by multiple enzyme systems such as glutathione peroxidase (GPx) and glutathione reductase (GR).…”
Section: Introductionmentioning
confidence: 99%
“…65 Particularly, lipid peroxidation is considered as the main mechanism by which ROSinduced impairment of testicular function is observed. 66 In the present study, the dose-and time-dependent testicular (seminiferous tubule) degenerative changes and DNA damage (dsDNA breaking detected by DNA comet) induced by oxidative stress (ie, high total ROS level and iNOS expression) and antioxidant depletion (ie, low ascorbate concentration and Nrf2 expression) upon nicotine/CS exposure suggested that oxidative burden is the most stringent criteria for maintaining tissue integrity during exposure. 67,68 Further, the dose-dependent DNA strand break due to the formation of peroxylnitrate indicates that nitric oxide (NO)-mediated pathogenesis may play a vital role in tobacco-associated conditions.…”
Section: -64mentioning
confidence: 48%